Oxides Film Formed on Fe- and Ni-Based Alloys: An Ellipsometry Insight - Benaioun, Noureddine; Gilliot, Mickaël; Lazar, Florica Simescu; Bubendorff, Jean-Luc; Hadjadj, Aomar (Coatings, 2023)
UV-visible spectroscopic ellipsometry was used to study the thickness and composition of the oxidized zone in Fe- and Ni-based alloys as a function of oxygen partial pressure. In the case of AISI 304 stainless steel, the weathered thickness increases with oxygen partial pressure, whereas in the case of Inconel 600, it appears to be independent of oxygen pressure. This trend is confirmed by the AFM measurements. For both materials studied, the oxygen-modified zone consists of two layers as confirmed by glow discharge optical emission spectrometry (GDOES) measurements. The thicknesses of these two layers vary differently on either side of an oxygen partial pressure of 0.1 Torr. In the case of AISI 304 stainless steel, the thickness of the Fe-rich outer layer decreases in favor of the Cr-rich inner layer. In the case of Inconel 600, the trend is reversed. The Ni-rich outer layer increases significantly above this critical pressure, while the Cr-rich inner layer decreases slightly. The composition of each layer in the oxidized zone is discussed in terms of its dielectric function in relation to reference material. The use of UV-visible ellipsometry as a non-destructive tool to study the structure and composition of the oxide bilayer of absorbing systems such as the alloys under investigation is a first.
Number: 5
Keywords: AFM; AIS 304; Cr_2O_3; Fe_2O_3; Inconel 600; NiO; ellipsometry; oxidation